Unveiling obstacles in virtual English education: echoes from Vietnamese learners - Le Thanh Thao; Le Xuan Mai; Pham Trut Thuy (Erudita)
After the COVID-19 pandemic, online learning in Vietnam has been paid more attention to. Consequently, this current qualitative study was conducted to investigate problems in English online classes in the Vietnamese context. Semi-structured interviews were used to collect data from six EFL students learning in a tertiary institution in the Southwest of Vietnam. The current study found some challenges the students often faced when learning online, categorized by three groups, namely teacher-related challenges, student-related challenges, and teacher-and-student living condition-related challenges. Regarding teacher-related challenges, teachers’ lack of abilities to use ICT tools and their attitudes towards teaching online negatively affected the EFL students’ online learning. Regarding student-related challenges, students’ resistance to the transmission from face-to-face learning to online learning and their low motivation played the role of barriers to their performance in online learning. For the final dimension, teacher-and-student condition-related challenges, insufficient teaching and learning devices, low internet connection, or noise did not allow the students to maximize their learning progress.